Computational Design of Molecularly Imprinted Polymers in Drug Delivery Systems: A Comprehensive Review - Singh, Gurpreet; Chawla, Pooja A.; Faruk, Abdul; Chawla, Viney; Kaur, Anmoldeep (Current Drug Delivery, 2023)
Background: Nowadays, biomedical research has been focusing on the design and development of new drug delivery systems that provide efficient drug targeting. The molecularly imprinted polymers (MIPs) have attracted wide interest and play an indispensable role as a drug carrier. Drug delivery systems based on MIPs have been frequently cited in the literature. They are cross-linked polymers that contain binding sites according to the complementary structure of the template molecules. They possess distinctive features of structure predictability and site recognition specificity. Versatile applications of MIPs include purification, biosensing, bioseparation, artificial antibodies, and drug delivery. An ideal MIPs should include features such as biocompatibility, biodegradability, and stability. Objective: In this article, we elaborate on the historic growth, synthesis, and preparation of different MIPs and present an updated summary of recent advances in the development of new drug delivery systems which are based on this technique. Their potential to deliver drugs in a controlled and targeted manner will also be discussed. Conclusion: MIPs possess unique advantages, such as lower toxicity, fewer side effects, and good therapeutic potential. They offer administration of drugs by different routes, i.e., oral, ocular or transdermal. Despite several advantages, biomedical companies are hesitant to invest in MIPs based drug delivery systems due to the limited availability of chemical compounds.
Keywords: density functional theory